Is type III prostatitis also associated with bacterial infection? - Song, Wei-Jie; Gao, Jun; Huang, Ji-Wei; Liu, Yuan; Long, Zhi; He, Le-Ye (Frontiers in Cellular and Infection Microbiology, 2023)
Objective To explore whether type III prostatitis is related to bacterial infection by detecting the composition and function of microorganisms in expressed prostatic secretion (EPS) of patients with chronic prostatitis (CP) and healthy people. Methods According to the inclusion and exclusion criteria, 57 subjects were included in our study, divided into the healthy group, type II prostatitis group, and type III prostatitis group. 16s rRNA sequencing technique was used to detect and analyze the microbial composition of EPS in each group. Additionally, the metagenomics sequencing technique was used to further explore the function of different bacteria in the type III prostatitis group. Data analysis was performed by bioinformatics software, and the results were statistically significant when P<0.05. Results Many microorganisms exist in EPS in both CP patients and healthy populations. However, the relative abundance of Pseudomonas, Haemophilus, Sneathia, Allobaculum, and Enterococcus in CP patients (including type II and III) were significantly different. Still, the relative abundance of different bacteria in type II prostatitis patients was much higher than in type III. The metagenomics sequencing results for the type III prostatitis group showed that the different bacteria had certain biological functions. Conclusion Based on our sequencing results and previous studies, we suggest that type III prostatitis may also be caused by bacterial infection.